The impact Of Ecological Tourism On Local Economies, Ecological Agriculture Farms In Turkey - Özgan, Burcu Beste (Int Scientific Conference Sgem, 14, Kilment Ohridsky Blvd, Sofia, 1797, Bulgaria, 2010)
Tourism sector provides employment to the 7% of workers in the world. It becomes a very important "export" opportunity in the countries where the level of income is low. Besides the benefits of tourism activities in local cultures and eco-systems. it also has irrecoverable negative effects. However, new opportunities provided by "alternative tourism" change this situation. Interests to travels having minimum negative effects on current natural and cultural richness and which are satisfactory in terms of educational and economic. are increasing gradually. ECEAT (European Center for Eco Agro Tourism) established as a foundation for the purpose of supporting the sustainable tourism in 1993, aims to assist to the farmers struggling in the small areas by bringing the people engaged in agriculture in natural condition in rural areas into action. In this study, the farms, camps, guest houses and small hotels operating in this sector in Turkey and members of ECEAT have been analyzed. Consequently, it is revealed that contribution of eco-tourism improving annually at the rate of between 10-50% to both Turkish economy and local economies is an important income resource in terms of promotion of our developing country and the economic value it is carrying. Based on this result, it is proved that tourism sector which has come up as a sector destroying the nature so far, may become a fundamental mean in the protection of nature when eco tourism is performed and managed in a good manner.
Keywords: Alternative tourism; Eco-tourism; echology; alternatif turizm; Eko-turizm